Analytical method for the determination of strychnine in tissues by gas chromatography/mass spectrometry: two case reports - Marques, E. P. (2000)
This paper describes an analytical method for strychnine determination in biological samples by gas chromatography/mass spectrometry and their application in the investigation of two cases involving strychnine ingestion: A fatal case and a clinical one. The strychnine is isolated from biological samples using a liquid-liquid extraction procedure. The clean-up procedure is performed using an acid solution. Papaverine is used as internal standard in the quantification of strychnine. In the analysed specimens, the limits of quantification were 0.1 [mu]g/ml or 0.1 [mu]g/g. The recovery rate ranged from 75.0% to 98.7% and the coefficients of variation ranged from 4.8% to 10.5%.